Wybrane nowoczesne koncepcje zarządzania jako czynniki skuteczności zarządzania strategicznego - Kubacka-Góral, Krystyna (Selected management conceptions as a factor of effectiveness of strategic management, 2007)
The aim of this paper is to describe the significance and the characterization of Knowledge Management, Balanced Scorecard, and conception of Consumption Chain. The article presents a few correlations between all of these conceptions allowing for increase the company’s competitiveness and effectiveness of strategic management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 86-99